Coexistence of Diabetic Retinopathy and Diabetic Foot in Patients Admitted at Indoor Facility of a Tertiary Care Center: Doi: 10.36351/pjo.v40i2.1782 - Matloob Rana, Afia; Yousafzai, Erum; gul, Humara; Akhter, Waseem (Pakistan Journal of Ophthalmology, 2024)
Purpose: To determine frequency of “diabetic retinopathy (DR)” in patients admitted at a tertiary care hospital with diabetic foot. Study Design: Cross sectional study. Place and Duration of Study: HBS medical and dental college, Islamabad from November 2022 to November 2023. Methods: Sixty two patients admitted with “diabetic foot ulcer”(DFU) were included in this study. Severity of DFU was assessed using . Patients were assessed for presence of “diabetic retinopathy (DR)” as well as its severity. Data was analyzed using SPSS 22. Results: Mean age was 49.37 ± 11.02 years. There were 34 (54.84%) males and 28 (45.16%) females. Mean HbA1C% was 9.46 ± 1.11%. Mean duration of diabetes was 10.06 ± 5.53 years. Forty five percent patients had diabetic retinopathy (DR). Amongst these patients diagnosed with DR (n = 45), 6 (13.33%) had mild non-proliferative DR, 20 (44.44%) had moderate non-proliferative DR, 14 (31.11%) had severe non-proliferative DR and 5 (11.11%) had proliferative DR. According to Wagner Grade there were 32 (51.61%), patients with grade 2 DFU, 19 (30.65%) had grade 1 and 11 (17.74%) had grade 3. Coexistence of diabetic retinopathy and diabetic foot in patients admitted at indoor facility was 72.58%. Conclusion: Prevalence of “diabetic retinopathy (DR)” in patients admitted with diabetic foot was 72.58%. Presence of diabetic foot can be considered as strong predictor of presence of concomitant “diabetic retinopathy”.